Alelopatia de cyperus rotundus L. en saccharum spp. cv. IAC-SP 93-6006 - Arevalo, R.A.=700 1 Bertoncini, E.I.; Salgado garcia, S.; Roái, F.
(Es, En)
Ilus., 10 ref.
Keywords: MALEZAS; ESCARDA; CYPERUS ROTUNDUS; ALELOPATIA; INHIBICION; SACCHARUM; CUBA